2023
DOI: 10.2147/cia.s424882
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Strategies for Retrograde Wire Tracking Failure via Poor Septal Collateral Channels in Chronic Total Occlusion

Cheng-Fu Wang,
Bao-Jun Chen,
Bo Luan
et al.

Abstract: Background Retrograde guidewire (GW) tracking success via a poor septal collateral channel (CC) when an antegrade approach fails is crucial for successful revascularization of coronary chronic total occlusion (CTO) with poor septal CC. However, the incidence, predictors, and management strategies for retrograde GW tracking failure via poor septal CC remain unclear. Methods In total, 122 CTO patients who underwent retrograde septal percutaneous coronary intervention (PCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As early as 2017, Dautov et al [24] reported that septal surfing was a safe and effective technique for crossing septal CCs regardless of Werner class. Then, a study by Wang et al [25] suggested that the success rate of retrograde guidewires tracking via poor septal CCs (Werner's CC0-1) was high, with a relatively high procedural success rate. They revealed that a CC diameter <1 mm, well-developed non-septal collateral, and LAD-CTO were independent predictors of guidewire tracking failure in patients undergoing retrograde CTO-PCI via poor septal CCs.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2017, Dautov et al [24] reported that septal surfing was a safe and effective technique for crossing septal CCs regardless of Werner class. Then, a study by Wang et al [25] suggested that the success rate of retrograde guidewires tracking via poor septal CCs (Werner's CC0-1) was high, with a relatively high procedural success rate. They revealed that a CC diameter <1 mm, well-developed non-septal collateral, and LAD-CTO were independent predictors of guidewire tracking failure in patients undergoing retrograde CTO-PCI via poor septal CCs.…”
Section: Discussionmentioning
confidence: 99%